The Problems of Economical Safety during the Formation of the Creative Cluster for a Region - KOKSHAROVA, Alyona Sergeevna; VANCHIKOVA, Elena Nikolaevna; RUBAN, Vladimir Alekseevich; BAGINOVA, Viktoriya Matveevna; SHARALDAEVA, Irina Arkhipovna (Journal of Advanced Research in Law and Economics, 2017)
The competitiveness of a region is defined mainly by the efficiency of using the possibilities of producing and promotion of products at the local level and not by the comparative advantages that are provided by geographical factors. In the context of globalization, the regions compete not only within the limits of one country but at the international level as well; there is a growing need for applying the methods and principles allowing to effectively use the existing advantages for taking and keeping the profitable positions at the market. In the context of the fourth industrial revolution, the main resource of national wealth is public infrastructure creating the appropriate environment for potential realization of the key element of public development meaning the creative and intellectual abilities of each person. That is why nowadays, the strategy of region development targeting the competitiveness growth quite often includes such a direction of development as forming the creative cluster. Nevertheless, there is no clear understanding which industries should be defined as creative, what is the way of forming these clusters of creative industries, and also what issues of economical safety can be faced by the regions during this process . This current research is aimed to find the solution of the current situation.